2015
DOI: 10.1007/s10880-015-9447-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stigma and Social Support on Development of Post-traumatic Growth Among Persons Living with HIV

Abstract: Given high rates of trauma in people living with HIV (PLH) and the health benefits of posttraumatic growth (PTG), understanding how to foster PTG in PLH exposed to trauma could be of interest to clinical psychologists working with this population. The current study examined factors theoretically related to development of PTG in PLH, namely HIV-related stigma, disclosure of HIV status, and emotional support. A sample of 334 HIV-positive adults answered a battery of self-report questionnaires. HIV-related stigma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
3
30
0
1
Order By: Relevance
“…However, despite all the difficulties recognized by the patients, some exhibited post-traumatic growth. Similarly, results of a study on HIV-positive people showed that patients who disclosed their disease to their partners and were supported spiritually exhibited higher post-traumatic growth (Kamen et al, 2015). Another study on the experiences of HIV patients in Saudi Arabia showed that most of the participants were more religious and frequently used spirituality as a means of coping (Omer, Lovering, & Al Shomrani, 2014…”
Section: Discussionmentioning
confidence: 96%
“…However, despite all the difficulties recognized by the patients, some exhibited post-traumatic growth. Similarly, results of a study on HIV-positive people showed that patients who disclosed their disease to their partners and were supported spiritually exhibited higher post-traumatic growth (Kamen et al, 2015). Another study on the experiences of HIV patients in Saudi Arabia showed that most of the participants were more religious and frequently used spirituality as a means of coping (Omer, Lovering, & Al Shomrani, 2014…”
Section: Discussionmentioning
confidence: 96%
“…Turan et al 80 found that the level of perceived HIV-related stigma in the community experienced by PLWH may cause adverse health and psychosocial outcomes. Social isolation and stigma might exacerbate symptoms of PTSD 81. In high-income countries, PLWH may experience ‘compound’ or ‘layered’ stigma, where stigmatising beliefs are associated with HIV infection and related to sexual orientation, commercial sexual behaviours, etc 82.…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic growth has also been found to be experienced by PLWH and research shows this has a positive effect on health outcomes. However, there is a paucity of research looking at posttraumatic growth, perceived stigma and disclosure regret together, meaning that a full understanding of the relationship is not clear [ 1 , 2 ]. This study sought to determine whether posttraumatic growth continues to have a positive effect on adjustment once perceived stigma and disclosure regret are accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the effects of posttraumatic growth is expanding, however, the relationship between perceived stigma, disclosure regret and posttraumatic growth is still developing. This research has shown a negative association of perceived stigma with posttraumatic growth [ 1 , 2 , 34 ]. Some studies also looked at the relation of disclosure and posttraumatic growth and found a positive relation, however, disclosure regret was not measured [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation